Learning motivation mediates student engagement and academic outcomes in digital higher education - Alfa Santoso Budiwidjojo Putra; Moyo Hady Poernomo; Ambar Kusuma Astuti; Purnawan Hardiyanto (Institute of Computer Science (IOCS), 2026)
The rapid expansion of digital learning in higher education has created new challenges in maintaining student engagement, academic performance, and satisfaction. While previous studies have widely examined the relationship between student engagement and academic outcomes, limited research has explored the psychological mechanisms that explain how engagement influences both academic performance and student satisfaction in digital learning contexts. This study investigates the mediating role of learning motivation in the relationship between student engagement, academic performance, and student satisfaction in digital higher education. A quantitative research design was employed using survey data collected from undergraduate students at a university in Indonesia. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings show that student engagement positively influences learning motivation, which subsequently improves academic performance and student satisfaction. Learning motivation also acts as a key mediating mechanism linking student engagement to both outcomes. These findings highlight the importance of strengthening students’ motivation to enhance learning effectiveness and satisfaction in digital learning environments.